Pengaruh Media Pembelajaran E-Learning Terhadap Disiplin Siswa Di Madrasah Aliyah Yasmu Manyar Gresik - Sahlan, Mohammad; Ladamay, Man Arfa; Yusuf Sya'bani, Mohammad Ahyan (STIT Muhammadiyah Paciran, 2021)
E-learning learning media is an activity of teaching and learning process by utilizing information and communication technology such as computers or smart phones. The implementation of learning at Madrasah Aliyah Yasmu Manyar has been carried out online or online since the covid-19 pandemic by utilizing information technology media, based on the circular letter of the ministry of education and culture no. 4 of 2020, in implementing online or online learning, students tend to be less active. The factors that cause student learning activity to decrease in online/online learning that result in decreased student discipline include: 1) lack of direct supervision (control) by the teacher towards students. 2) there is no awareness from students regarding the importance of participating in online/online learning. 3) there is no awareness from parents to encourage students to be more active in participating in online/online learning. With the formulation of the problem as follows: 1) How is the implementation of e-learning learning media at Madrasah Aliyah Yasmu for students? 2) How is the influence of e-learning learning media on student discipline at Madrasah Aliyah Yasmu?. The research in this thesis uses a quantitative approach, the data analysis technique is obtained through the product moment correlation analysis technique, which is processed by the SPSS calculation application. This study aims to determine how much influence the e-learning media has on student discipline. The population in this study were 135 students. The number of samples used is random sampling, namely 57 respondents. The data collection technique used is a questionnaire. The results showed that the e-learning learning media had a positive effect on student discipline, namely 15.6% and the remaining 84.4% had no effect on student discipline.